THE HALAL FOOD MOVEMENT IN ENHANCING HALAL-CERTIFIED MSMES IN MEDAN CITY USING THE "HALAL FOOD" MOBILE APPLICATION - Siregar, Achmad Zulfikar; Rahmi, Elvika; Sari, Ika Yusnita; Dewi, Komala (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2024)
The community pays great attention to the halal status of the food or beverages they choose to consume. A halal certificate is a written fatwa from the Indonesian Ulema Council (MUI) that declares the halal status of a product in accordance with Islamic law. This is due to the high public interest in halal food and beverages.  Thus, the application of developing technology is very much needed in the current era. The goal is for visitors/tourists to easily find halal-certified food or beverages. This system is built using the waterfall method with data from MSME in Medan City. The designed application can be accessed on a mobile basis, making it easy for all users to use. The results of this research can help MSME register food or beverage products into the application, allowing visitors/tourists to easily find products that are certified halal using the mobile-based halal food application, GEMAH.